De-masking oxytocin-deficiency in craniopharyngioma and assessing its link with affective function. (February 2018) - Gebert, Dorothea; Auer, Matthias K.; Stieg, Mareike R.; Freitag, Martin T.; Lahne, Madlén; Fuss, Johannes; Schilbach, Katharina; Schopohl, Jochen; Stalla, Günter K.; Kopczak, Anna
Highlights: Oxytocin is only reduced in craniopharyngioma patients with hypothalamic damage. Stimulation reveals an oxytocin-deficiency in all craniopharyngioma patients. Diabetes insipidus is not a suitable proxy for oxytocin deficiency. Higher baseline oxytocin is linked with higher trait anxiety. A blunted oxytocin-response to stimulation is linked with higher state anxiety. Abstract: Despite the high prevalence of panhypopituitarism and diabetes insipidus in patients with craniopharyngioma (CP), little is known about the functioning of the neuropeptide oxytocin in these patients. This is of special interest as tumor-associated lesions often impair sites critical for oxytocin production and release, and affective dysfunction in CP links with elsewhere reported prosocial, antidepressant and anxiolytic oxytocin effects. Using a prospective study-design, we tested whether oxytocin is reduced in CP-patients, and whether altered oxytocin levels account for affective and emotional dysfunction. 26 adult CP-patients and 26 healthy controls matched in sex and age underwent physical exercise, a stimulus previously shown to induce oxytocin release. Baseline and stimulated salivary oxytocin levels, as well as empathy, depression and anxiety scores were measured. Results showed that patients overall did not present with lower baseline oxytocin levels than controls ( F [1, 30] = 0.21, p = 0.649), but baseline oxytocin levels were indeed reduced in patients with hypothalamic damage, as assessed by MRI-based grading ( F [2, 9.79] = 4.54, p  = 0.040). In response to exercise-induced stimulation, all CP-patients showed a blunted oxytocin-release compared to controls ( F [1, 30] = 9.36, p  = 0.005). DI was not associated with oxytocin levels. Regarding affective function, unexpectedly, higher baseline oxytocin was related to higher trait anxiety ( b  = 2.885, t (43) = 2.421, p  = 0.020, CI[.478; 5.292]); the positive link with higher depression failed to reach statistical significance ( b  = 1.928, t (43) = 1.949, p  = 0.058, CI[−0.070; 3.927]). A blunted oxytocin-release was linked with higher state anxiety ( b  = −0.133, t (43) = −2.797, p  = 0.008, CI[-0.230; −0.037]). Empathy was not associated with oxytocin measures. In conclusion, we observed reduced baseline oxytocin levels only in CP-patients with hypothalamic damage. Exercise-induced stimulation de-masked an oxytocin-deficiency in all CP-patients. Baseline oxytocin levels and stimulated OT-responses might have different effects on affective function, which should be considered in future substitution paradigms.